3D plasmonic nanobowl platform for the study of exosomes in solution. Issue 20 (28th May 2015) - Lee, Changwon; Carney, Randy P.; Hazari, Sidhartha; Smith, Zachary J.; Knudson, Alisha; Robertson, Christopher S.; Lam, Kit S.; Wachsmann-Hogiu, Sebastian
<x xml:space="preserve">Abstract</x> Nanobowl substrates are used to capture exosomes for SERS measurements that can provide biochemical analysis of intact and ruptured exosomes.